Notes on Early Land Plants Today. 54. A transfer in Lepidoziaceae (Marchantiophyta) - Cooper, Endymion D.; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2014)
When Cooper et al. (2013) reorganized species among genera in Lepidoziaceae Limpricht (1876: 310), one taxon, Lepidozia leratii Stephani (1922: 333), was mistakenly combined under Neolepidozia Fulford & Taylor (1959: 81). The transfer was not based on any morphological or molecular evidence placing it in Neolepidozia. On the contrary, molecular phylogenetic studies (Cooper et al., 2011, 2012; Heslewood & Brown, 2007) all place Lepidozia leratii in close proximity of Tricholepidozia pulcherrima (Stephani 1909: 600) E.D.Cooper in Cooper et al. (2013: 60) the type of Tricholepidozia (Schuster 1963: 256) E.D.Cooper in Cooper et al. (2013: 58). This error is corrected here.